Sen’s Apples: Commitment, Agent Relativity and Social Norms - Peacock, Mark S.; Justus Liebig University Giessen (My University, 2011)
This paper examines Amartya Sen’s notion of ‘commitment’ in light of Geoffrey Brennan’s recent discussion thereof. Its aim is to elucidate one type of commitment which consists in following social norms. To this end, I discuss Sen’s ‘apples’ example from his ‘Rational fools’ essay (section 2). In section 3, I draw some implications of commitments in Sen’s work for the concept of ‘agent relativity’. Section 4 discusses the distinctiveness of Sen’s conception of human beings in their supposed ability to be able to bind themselves to following social norms at the expense of their own benefit.
Keywords: ddc:100; ddc:330